Mass transfer in Taylor flow: Transfer rate modelling from measurements at the slug and film scale. (August 2018) - Butler, C.; Lalanne, B.; Sandmann, K.; Cid, E.; Billet, A.-M.
Highlights: Mass transfer in non-reactive gas–liquid Taylor flow studied with PLIF-I and PIV. Gas and liquid were injected by T-mixer into channel of circular cross-section. Two contrasted regimes were observed in liquid slug with transition at Re  300. Contaminants potentially cause fluctuations at bubble rear and enhance mixing in slug. A new scaling law for overall mass transfer is proposed which relates Sh to Re and Sc . Abstract: Mass transfer in non-reactive gas–liquid Taylor flow has been studied at the unit cell scale with high resolution non-invasive experimental techniques for a large variety of hydrodynamic regimes at high inertia (30 ≤  Reb  ≤ 1430). The planar laser induced fluorescence with inhibition (PLIF-I) technique has been used to measure the local oxygen concentration fields in different liquid phases (tap water, water and Breox solutions at different concentrations) in order to vary the Schmidt number Sc . The concentration field can be separated into a film region, corresponding to the thin lubrication film extended all along the channel wall, and the remainder of the liquid which makes up the slug region. It has been found that even though the global mass transfer is mainly driven by the rate of transfer in the slug, the film plays a significant role as a source of oxygen, in addition to the bubble caps, to feed the slug. In the investigated circular capillary, fed by means of a T-mixer, two contrasted configurations have been observed in the liquid phase (slugs and films), depending on a critical bubble Reynolds number of  ∼ 300, where the time-averaged concentration fields are found to differ considerably. For large Reynolds number, particle image velocimetry (PIV) measurements have revealed low temporal fluctuations at the rear of the bubble, possibly due to the presence of adsorbed contaminants, that tends to increase mixing in the slug. Despite this difference, the mass transfer dynamics were found to be controlled in all cases by the intensity of the recirculating motion in the slug, which is directly related to the bubble velocity for these cases of thin films. A new scaling law has been proposed for the overall Sherwood number, based on Reb and Sc, which satisfactorily describes the overall mass transfer of the experimental results for Reb  > 120 to an accuracy of ±11%.